Overexpression of METAL TOLERANCE PROTEIN8 reveals new aspects of metal transport in Arabidopsis thaliana seeds. (21st September 2021) - Höller, S.; Küpper, H.; Brückner, D.; Garrevoet, J.; Spiers, K.; Falkenberg, G.; Andresen, E.; Peiter, E.
Abstract: METAL TOLERANCE PROTEIN8 (MTP8) of Arabidopsis thaliana is a member of the CATION DIFFUSION FACILITATOR (CDF) family of proteins that transports primarily manganese (Mn), but also iron (Fe). MTP8 mediates Mn allocation to specific cell types in the developing embryo, and Fe re‐allocation as well as Mn tolerance during imbibition. We analysed if an overexpression of MTP8 driven by the CaMV 35S promoter has an effect on Mn tolerance during imbibition and on Mn and Fe storage in seeds, which would render it a biofortification target. Fe, Mn and Zn concentrations in MTP8 ‐overexpressing lines in wild type and vit1‐1 backgrounds were analysed by ICP‐MS. Distribution of metals in intact seeds was determined by synchrotron µXRF tomography. MTP8 overexpression led to a strongly increased Mn tolerance of seeds during imbibition, supporting its effectiveness in loading excess Mn into the vacuole. In mature seeds, MTP8 overexpression did not cause a consistent increase in Mn and Fe accumulation, and it did not change the allocation pattern of these metals. Zn concentrations were consistently increased in bulk samples. The results demonstrate that Mn and Fe allocation is not determined primarily by the MTP8 expression pattern, suggesting either a cell type‐specific provision of metals for vacuolar sequestration by upstream transport processes, or the determination of MTP8 activity by post‐translational regulation. Abstract : Overexpression of the vacuolar transporter MTP8 entails increased tolerance to high Mn levels during seed imbibition, but does not alter Mn and Fe accumulation and allocation.